Migration intentions and their impact on healthcare workers in a Lebanese public university hospital amid crises: A mixed-method study - Linda Abou-Abbas; Maya Hassan; Elizabeth Al Mounajed; Mohamad Shafic Ramadan; Hala Dalal (PLoS ONE, 2026)
Background The emigration of skilled healthcare workers (HCWs) seeking better opportunities poses major challenges to healthcare systems in low- and middle-income countries. Amidst ongoing economic and political crises, Lebanon is facing substantial healthcare workforce migration. This study explored the migration intentions of Lebanese HCWs, identifies key drivers, and proposes context-specific retention strategies. Methods A mixed-methods design was employed at Rafik Hariri University Hospital (RHUH) in Beirut, Lebanon. A structured survey assessed migration intentions and associated drivers among frontline healthcare workers, while semi-structured interviews with department chiefs explored organizational and systemic factors influencing workforce retention. Quantitative data were analyzed to identify predictors of migration intentions, and qualitative data were thematically analyzed using a combined deductive–inductive approach. Results Among 120 HCWs surveyed, 70% expressing intentions to migrate—primarily due to financial concerns (93%) and security issues (81%). Lower satisfaction with pay (adjusted OR= 0.85, 95% CI = 0.72–0.996) was significantly associated with migration intentions. Qualitative findings confirmed widespread staff migration since 2019, leading to critical shortages, heavier workloads, and department closures. Department chiefs emphasized the need for financial incentives, professional development opportunities, supportive management, and flexible scheduling to improve retention. Conclusions HCW migration from Lebanon reflects a complex interplay of financial, professional, and systemic factors. Immediate and sustainable policy interventions—combining financial stabilization with workforce development and improved working conditions—are urgently required to preserve healthcare system functionality and resilience.